PENGARUH LAMA PENIRISAN TERHADAP DAYA SIMPAN BENIH KAKAO (THEOBROMA CACAO L.) - PUTRI DARMAWATI, IDA AYU; NGURAH RAKA, I GUSTI; KETUT AGUNG, IDA BAGUS (AGRITROP, 2012)
This experiment was carried out at Laboratory of Seed Technology, Agronomy Department, Faculty of Agriculture, Udayana University. The aim of this experiment was to find out the effect the airing periods on seeds water content, storability and viability of cacao seeds. Wet sawdust (60% water content) was used to keep the cacao seeds in storage. The cacao seeds was airing in four level before storing, those are: 1) without airing, 2) airing in two days, 3) airing in four days, and 4) airing in six days. The completely randomized design with six replications was used in this experiment. Every three days along the 30 days storage periods, the percentage of seeds germinated in storage, seeds water content, seeds germination, the unison of seedling growth, and the performance of seedling (leaf number, height, long of primary root, and totally of seedling dry weight) were detected. The storing using sawdust (60% water content) can save the viability and vigor of cacao seeds which is by six days airing experience. Storing seeds as long as 15 days can save the seeds germination by the rate of more than 80%, and up to 50% seeds germination rate can be save on the 21 days store periods. Storing seeds as long as 9 days can save the cacao seeds vigor?s (with the variable of unison of seedling growth) by the rate of more than 80%. The seedling performances were not significant differences between the level of airing treatment, which is detected every 3 days along 30 days store periods.
Keywords: Airing Periods, Stoability, Cacao (Theobroma cacao L.), Seeds